مسح التطورات الاقتصادية والاجتماعية في المنطقة العربية 2013-2012 - United Nations Economic; Social Commission for Western Asia (United Nations, 2014)
The Survey of Economic and Social Development in the Arab Region 2012-2013 assesses the most recent economic and social developments of Arab countries, using the data that became available by the 2nd quarter of 2013. The immediate policy challenge for most of Arab countries is to create employment without relying on an expansionary fiscal and monetary policy mix. The Survey finds that several policy options are available for this policy challenge even in this highly uncertain situation surrounding the region’s socioeconomic development. In parallel to the specific policy proposals, the Survey emphasizes the importance of policy dialogue in the area of employment and more constructive regional integration framework on this subject. The revival of regional leverage along this line of reform needs be encouraged to halt the polarization by stabilizing the region’s socioeconomic development paths for all Arab countries.